Zenkovia, a new generic replacement name for preoccupied Scaphella Zenkova, 1977 (Ostracoda) non Swainson, 1832 (Gastropoda) - Doweld, Alexander B. (Zootaxa, 2013)
The generic name Scaphella was proposed by Zenkova (1977: 81; type species S. gibbosa Zenkova, by original designation) for a new fossil ostracod genus from the Middle Silurian (Wenlockian) of the eastern slope of Middle Urals (Russian Federation). However, this name is already preoccupied by a marine gastropod molluscan generic name Scaphella Swainson (1832: pl. 87), which is in active current use in zoology (Bail & Poppe 2001; Bail 2013) and even served as a type of a distinct molluscan subfamily Scaphellinae Gray (1857) [Mollusca: Gastropoda: Caenogastropoda: Neogastropoda: Muricoidea: Volutidae: Scaphellinae].